Escherichia coli mutants with an altered sensitivity to cecropin D. - Sidén, I (1983)
Cecropins are a family of small, basic antibacterial polypeptides which can be isolated from pupae of immunized Lepidoptera. They are active against both gram-negative and gram-positive bacteria. We studied a mutant of Escherichia coli, strain SB1004, which is more sensitive to cecropin D than is the parental strain. The mutant was selected as resistant to a host range mutant of a Serratia marcescens phage. When the protein composition of the outer membrane was examined, strain SB1004 and some other phage-resistant mutants were found to be deficient in the OmpC protein. It was concluded that the OmpC protein is the receptor of the phage. Strain SB1004 was found to differ from other ompC mutants in being especially sensitive to hydrophobic antibiotics and to cecropin D. Furthermore, strain SB1004 has a tendency for spontaneous autolysis. A genetic analysis showed the mutations in strain SB1004 and a suppressor mutant to map in the ompC region. The activity of cecropin D against different strains of E. coli was specifically enhanced when divalent cations were absent. No such effect was found with cecropins A and B, which are less hydrophobic than the D form.